Antihyperglycemic Effectiveness of Ethanolic Extract of Takokak Fruit (Solanum Torvum Swartz) on Male White Rats (Rattus Norvegicus) Induced by Glucose - Rahmat Ismail; Ahlan Sangkal (Lembaga Pengembangan Kinerja Dosen, 2025)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels resulting from impaired insulin secretion, insulin resistance, or a combination of both. This condition requires long-term treatment and has the potential to lead to serious complications if not properly managed. The search for alternative herbal-based treatments has become a major focus of various pharmacological studies. One such plant with potential is the takokak fruit (Solanum torvum Swartz), which has traditionally been used to treat various health conditions such as hypertension, microbial infections, and reproductive system disorders, as well as possessing antipyretic and antidiabetic properties. This study aimed to evaluate the antihyperglycemic efficacy of the takokak fruit ethanol extract in glucose-induced male white rats (Rattus norvegicus). The extract was obtained through a maceration method using 96% ethanol as a solvent. Five test groups were prepared, each consisting of three rats: a negative control group (Na-CMC), a positive control group (metformin), and three treatment groups with takokak extract concentrations of 5%, 10%, and 20%. Glucose induction was administered orally, and after 30 minutes, the extract was administered to the treatment group, and blood glucose levels were measured for two hours. The results showed that the takokak fruit extract was able to reduce blood sugar levels by 27% in the 5% group, 25% in the 10% group, and 33% in the 20% group, respectively. However, the ANOVA statistical test yielded a significance value of 0.48, indicating that the difference in blood glucose reduction between the groups was not statistically significant. Although not yet significant, these results indicate that the ethanol extract of takokak fruit has potential as an antihyperglycemic agent, which requires further research on a larger scale and duration to obtain more conclusive results.